Do Freight Rates for Produce and Ornamentals Cover Costs? - Richard Beilock (EDIS)
Over 99% of Florida's interstate produce and ornamentals shipments are by truck. As such, it is important to Florida agriculture that these carriers be financially viable. At the same time, shipper/receivers are interested in paying the least cost possible for haulage. They are also interested in having reliable motor carrier service, which is only possible if freight rates are sufficient to cover costs. In this report, the adequacy of freight rates paid for produce and ornamentals movements out of Florida and freight rates received for complementary haulage into the state will be examined. Data come from a 2001/2002 survey of over 1,600 drivers of semis as they exited the Florida Peninsula (Appendix; Beilock, 2004).  This is EDIS document, FE541, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2005.